The Ca2+ Sensor Calcineurin B–Like Protein 10 in Plants: Emerging New Crucial Roles for Plant Abiotic Stress Tolerance - Plasencia, Felix A.; Estrada, Yanira; Flores, Francisco B.; Ortíz-Atienza, Ana; Lozano, Rafael; Egea, Isabel (Frontiers in Plant Science, 2021)
Ca2+ is a second messenger that mediates plant responses to abiotic stress; Ca2+ signals need to be decoded by Ca2+ sensors that translate the signal into physiological, metabolic, and molecular responses. Recent research regarding the Ca2+ sensor CALCINEURIN B-LIKE PROTEIN 10 (CBL10) has resulted in important advances in understanding the function of this signaling component during abiotic stress tolerance. Under saline conditions, CBL10 function was initially understood to be linked to regulation of Na+ homeostasis, protecting plant shoots from salt stress. During this process, CBL10 interacts with the CBL-interacting protein kinase 24 (CIPK24, SOS2), this interaction being localized at both the plasma and vacuolar (tonoplast) membranes. Interestingly, recent studies have exposed that CBL10 is a regulator not only of Na+ homeostasis but also of Ca2+ under salt stress, regulating Ca2+ fluxes in vacuoles, and also at the plasma membrane. This review summarizes new research regarding functions of CBL10 in plant stress tolerance, predominantly salt stress, as this is the most commonly studied abiotic stress associated with the function of this regulator. Special focus has been placed on some aspects that are still unclear. We also pay particular attention on the proven versatility of CBL10 to activate (in a CIPK-dependent manner) or repress (by direct interaction) downstream targets, in different subcellular locations. These in turn appear to be the link through which CBL10 could be a key master regulator of stress signaling in plants and also a crucial participant in fruit development and quality, as disruption of CBL10 results in inadequate Ca2+ partitioning in plants and fruit. New emerging roles associated with other abiotic stresses in addition to salt stress, such as drought, flooding, and K+ deficiency, are also addressed in this review. Finally, we provide an outline of recent advances in identification of potential targets of CBL10, as CBL10/CIPKs complexes and as CBL10 direct interactions. The aim is to showcase new research regarding this master regulator of abiotic stress tolerance that may be essential to the maintenance of crop productivity under abiotic stress. This is particularly pertinent when considering the scenario of a projected increase in extreme environmental conditions due to climate change.